2018
DOI: 10.1371/journal.pone.0207006
|View full text |Cite|
|
Sign up to set email alerts
|

The beginning of the end: A qualitative study of falls among HIV+ individuals

Abstract: Falls are an important concern for individuals living with HIV (HIV+). The purpose of this study was to understand perceptions of HIV+ individuals who had fallen regarding what caused their falls, prevention strategies that they used, and the impact of falls on their lives. Qualitative Description was the approach best suited to our study. We conducted in-depth interviews with 21 HIV+ individuals aged 47 to 71 years who had fallen within the past two years and who received care in a primary care/HIV clinic. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Six studies (43%) used longitudinal prospective cohort design, 16 24 27–30 four studies (29%) used cross-sectional design, 26 31–33 one study was a secondary analysis of data from a longitudinal prospective cohort study, 34 one study was a longitudinal retrospective analysis of patient databases, 35 while another used qualitative methods. 1 One systematic review was also included. 36 Four studies (29%) 24 27 30 32 had samples consisting of both PLWH and HIV-seronegative participants (SNP).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies (43%) used longitudinal prospective cohort design, 16 24 27–30 four studies (29%) used cross-sectional design, 26 31–33 one study was a secondary analysis of data from a longitudinal prospective cohort study, 34 one study was a longitudinal retrospective analysis of patient databases, 35 while another used qualitative methods. 1 One systematic review was also included. 36 Four studies (29%) 24 27 30 32 had samples consisting of both PLWH and HIV-seronegative participants (SNP).…”
Section: Resultsmentioning
confidence: 99%
“…Another study 28 identified peripheral neuropathy as a potential confounder for the association between falls and frailty in PLWH. In one qualitative study, 1 PLWH reported peripheral neuropathy in addition to opportunistic infections, spinal stenosis, arthritis, stroke, hepatic encephalopathy as being causes of their falls. Only one study 24 failed to find an association between peripheral neuropathy and falls and attributed it to their relatively younger cohort being potentially better able to compensate for neuropathies or possibly less sensitive tests being used to determine peripheral neuropathy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations